AB0844 SERUM sCD40L LEVEL CAN PREDICT SHORT-TERM CLINICAL OUTCOMES IN PATIENTS WITH PSORIATIC ARTHRITIS ON TREATMENT WITH APREMILAST. (2nd June 2020) - Venerito, V.; Natuzzi, D.; Bizzoca, R.; Lacarpia, N.; Fornaro, M.; Giannotta, M.; Righetti, G.; Lopalco, G.; Iannone, F.
Abstract : Background: The pathogenesis of Psoriatic Arthritis (PsA) involves several pathways simultaneously, including the CD40/CD40L interaction. In vitro evidence suggests that the cleavage of soluble CD40L (sCD40L) may happen as a Phosphodiesterase 4- (PDE4) dependent reaction [1-3]. Objectives: Here we investigate whether apremilast, a PDE4 inhibitor, could modify circulating level of soluble CD40L (sCD40L) in PsA patients, and the possible associations of these changes with clinical response. Methods: Consecutive patients with PsA starting apremilast in routine clinical practice between October 2018 and September 2019 in a single center were longitudinally observed. Sera were collected at baseline and at the 6-month follow up visit. Demographics and clinical characterstics at different observation times were recorded. Samples were ran in a Bio-Plex ProTM plate for sCD40L level. To investigate the association of sCD40L level with DAPSA minor response and DAPSA Low Disease Activity (LDA) and/or Remission (ie DAPSA ≤14) at 6 months of treatment, multivariate logistic regression models with backward selection (p <0.05) were built. Results: We studied n.27 patients (16/27 women, 59.6%) with PsA with mean age (± SD) of 58.4 ± 10.4 years. A significant reduction of the mean values of DAPSA, LEI and PASI was evidenced at 6 months. Mean serum level of sCD40L decreased from 5364.02 ± 2025.70 to 4412.14 ± 2629.81 pg/ml after 6 months of apremilast treatment (p=0.01, Figure 1 ). Baseline sCD40L was an independent predictor of DAPSA minor response (OR 1.0006, 95% CI 1.0001-1.0012; AUC 0.76 (95% CI 0.55-0.97)). Moreover baseline DAPSA (OR 0.80, 95% CI 0.65-0.98) and baseline sCD40L (OR 1.001, 95%CI 1.0001-1.0028; AUC 0.85 95% CI 0.69-0.98, Figure 2 ) were independently associated with DAPSA LDA/Remission. Conclusion: Apremilast may decrease sCD40L level in PsA patients. Higher baseline serum sCD40L level may predict short-term clinical response to apremilast. References: [1]Davidson DC, Jackson JW, Maggirwar SB. Targeting platelet-derived soluble CD40 ligand: a new treatment strategy for HIV-associated neuroinflammation? J Neuroinflammation 2013;10:144. [2]Vanichakarn P, Blair P, Wu C, Freedman JE, Chakrabarti S. Neutrophil CD40 enhances platelet-mediated inflammation. Thromb Res 2008;122(3):346-58. [3]Totani L, Amore C, Di Santo A, et al. Roflumilast inhibits leukocyte-platelet interactions and prevents the prothrombotic functions of polymorphonuclear leukocytes and monocytes. J Thromb Haemost 2016;14(1):191-204. Disclosure of Interests: Vincenzo Venerito: None declared, Dorotea Natuzzi: None declared, Rita Bizzoca: None declared, Nunzia Lacarpia: None declared, Marco Fornaro: None declared, maria giannotta: None declared, giulia righetti: None declared, Giuseppe Lopalco: None declared, Florenzo Iannone Consultant of: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Speakers bureau: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD